The Implementation of PjBL Model in Semantics Course in Identifying Jambi Culture - Kusmana, Ade; Afria, Rengki (Indo-MathEdu Intellectuals Journal, 2023)
This study aims to analyze the implementation of the Project-Based Learning Model (PjBL) in the context of the Semantics course to explore the understanding and identification of Jambi Culture. The research method used was classroom action research involving 60 third semester students of the Indonesian Literature Study Program, FKIP Jambi University. Data collection was carried out through classroom observations, interviews, and analysis of project results. The data were analyzed qualitatively to evaluate the impact of the learning model on cultural understanding and identification. The results showed that the implementation of the PJBL Learning Model succeeded in increasing students' involvement in learning and deepening their understanding of Jambi culture. Students showed improved semantic analysis skills through projects that required in-depth understanding of aspects of Jambi culture